A Theoretical-Based Experimental Approach for Investigating the Charging of Insulators - Tareq H. Abbood; Hassan N. Al-Obaidi; Ali Mahdi; Wasan Kadhem; Faten Mousa; Huda Hussein (Journal of Engineering and Sustainable Development)
A theoretical-based experimental approach has been presented as a simplified tool for investigating the charging of insulators. Throughout this work, the Polyethylene Terephthalate (PET) material is chosen as a case study. The experiment is carried out using the scanning electron microscope (SEM) with a primary energy of 30 keV, an electron current of 1.3 nA, and a working distance of 15 mm. The suggested approach has been initiated by the spacemen-current as the first step. Keeping in mind that this parameter is by default recorded by the SEM machine itself. The total electron yield emission is then determined during the irradiating time in accordance with this. Subsequently, the consuming time, electron-trapped lifetime, trapped electrons, leakage, and displacement currents are evaluated. Results have clearly shown that the knowledge of the spacemen current can be used to provide excellent information to SEM users. Indeed, many of the characteristics factors that define the insulators can be evaluated with no more complicated experimental setup.